Isolation, structure modification, and anti-rheumatoid arthritis activity of isopimarane-type diterpenoids from Orthosiphon aristatus - Yong-Xin Luo; Xu Gong; Zhi-Cheng Su; Jin-Feng Mo; Dong-Li Li; Ri-Hui Wu; Jing-Wei Jin; Ming Lang; Jin-Ping Wang; Xue-Tao Xu; Li-She Gan (Journal of Enzyme Inhibition and Medicinal Chemistry)
Orthosiphon aristatus is a well-known folkloric medicine and herb for Guangdong soup for the treatment of rheumatism in China. Eight isopimarane-type and migrated pimarane-type diterpenoids (1-8), including a new one with a rarely occurring α,β-unsaturated diketone C-ring, were isolated from O. aristatus. Their structures were determined by spectroscopic methods and quantum chemical calculations. Furthermore, the most abundant compound, orthosiphol K, was structurally modified by modern synthetic techniques to give seven new derivatives (9-15). The anti-rheumatoid arthritis activity of these diterpenoids were evaluated on a TNF-α induced MH7A human rheumatoid fibroblast-like synoviocyte model. Compound 10 showed the most potent activity among these compounds. Based on their inhibitory effects on the release levels of IL-1β, the preliminary structure-activity relationships were concluded. Furthermore, western blot analysis revealed that 10 could increase the expression of IκBα and decrease the expression of NF-κB p65, and the expression levels of COX-2 and NLRP3 proteins were consequently down-regulated.